A sharp lower bound for the least eigenvalue of the signless Laplacian of a non-bipartite graph - Cardoso, D.M.
We prove that the minimum value of the least eigenvalue of the signless Laplacian of a connected non-bipartite graph with a prescribed number of vertices is attained solely in the unicyclic graph obtained from a triangle by attaching a path at one of its endvertices. © 2008 Elsevier Inc. All rights reserved.